Piękno nieliterackiego słowa Jana Pawła II = The beauty of non-literary texts of John Paul II - Seul, Anastazja (1961- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article "The beauty of non-literary texts of John Paul II" focuses its attention on artistic values of utilitarian works of John Paul II. The author indicates that the Pope in his homilies, exposes, personal utterances and also in official documents of the Church (encyclicals, Apostolic letters) used different stylistic features as means to express his thoughts.
Keywords: Jan Paweł II, papież (1929-2005); John Paul II; środki stylistyczne; retoryka; paralelizm; metafora; obraz poetycki; stylistic features; rhetoric; parallelism; metaphor; poetic expression